2022
DOI: 10.1155/2022/9641143
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Privacy Protection Standards for Smart Home

Abstract: With the rapid development of network technology, society has entered the Internet of Things (IoT) era. Enriching IoT devices enable smart home privacy information to be easily obtained through data mining. Smart home privacy protection (SHPP) has a far­reaching impact on the development of all aspects of society. Industrial and academic circles pay great attention to the privacy protection of the smart home, and the ability to protect the privacy needs to be improved. SHPP standards are one way to evaluate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Additionally, ten standards of IoT [36][37][38][39][40][41][42][43][44][45] are summarized in Table 3. The organizations involved include but are not limited to the IEEE, the ANSI, the ISA, the ISO, and the IEC.…”
Section: Standards Of Cps and Iotmentioning
confidence: 99%
“…Additionally, ten standards of IoT [36][37][38][39][40][41][42][43][44][45] are summarized in Table 3. The organizations involved include but are not limited to the IEEE, the ANSI, the ISA, the ISO, and the IEC.…”
Section: Standards Of Cps and Iotmentioning
confidence: 99%
“…For example, introducing intelligent home systems under the COVID-19 pandemic can facilitate caretakers to take care of particular groups [9][10][11]. The development of smart homes has likewise revealed many problems, privacy issues, operational issues, etc., that need to be resolved [12,13]. Globally the ageing population is increasing, and older consumers are changing their attitudes while wanting a higher quality of life [14].…”
Section: Introductionmentioning
confidence: 99%
“…The comprehension and perceptions of older users were low for menu grouping, but research has shown that interaction was not best using a single test [ 28 , 29 , 30 , 31 ]. In intelligent home service interaction systems, operational tasks are complex; they include increased interaction steps and high task failure rates for older users [ 32 , 33 , 34 , 35 ]. At the same time, the intervention of complex colours can also affect the efficiency of older users [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%